1156 Hypoxic Perinatal Cardiomyopathy-Diagnosis and Evolution. (October 2012) - Dimitiru, L; Dimitiru, AG; Stamatin, M
Abstract : Purpose: To present the main aspects of myocardial injury secondary to perinatal hypoxia. Methods/patients: 88 newborns aged 0–14 days, normal birth weight, with perinatal hypoxia (Apgar score 3–7), receveing resuscitation, without major congenital heart diseases. All cases: clinical exam, ECG, chest X-ray (Rx.CT), Doppler echocardiography (ECHO). Most of patients were evaluated and after 6 months. Results: The patients had mainly signs of neurological post hypoxic suffering, 8 cases signs of severe heart injury (cardiomegaly, respiratory distress, cyanosis, peripheric hypoperfusion), other cases: systolic murmur (64) and signs of PPHN (8). Chest X-ray: cardiomegaly (32). ECG: severe left ventricle (LV) repolarization disturbances and low voltage of QRS complexes (37), without ischemic changes. ECHO at 2–7 days of life: *the absence of severe congenital cardiac anomaly; *permeability of foramen ovalae (100%); mild to severe tricuspid insufficiency, RV and RA dilation (29); sometimes right-left shunt through the FO *myocardial hypertrophy (42) mainly IVS(29), signs of PPHN(6); increased myocardial performance index (44 cases), the systolic dysfunction (5) and severe LV diastolic dysfunction (45 cases). New evaluation at 6 months showed; reduction of the myocardial hypertrophy and of tricuspid regurgitation, normal LV systolic and diastolic function. Conclusions: The perinatal hypoxia can induce a important myocardial injury as hypoxic ischemic myocardopathy or transient post hypoxic hypertrophic cardiomyopathy (62.2% of patients), the signs of cardiovascular suffering missing often. Echo is the main method for diagnosis and follow up of perinatal hypoxic cardiomyopathy and is necessary performed from the first week of life.